CHINA'S STRATEGIC COMPETITION IN CYBERSPACE. VOLT TYPHOON AND SALT TYPHOON AS A PROJECTION OF POWER, A MORE AGGRESSIVE POSTURE AND A FUTURE BEYOND ESPIONAGE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
China’s strategic competition in cyberspace has evolved beyond traditional espionage, adopting a more aggressive posture that integrates cyber sabotage as a critical tool of statecraft. This paper examines the activities of the state-sponsored hacking groups Volt Typhoon and Salt Typhoon, highlighting its transition from intelligence gathering to disruptive cyber operations against critical infrastructure. By leveraging Living off the Land Binaries (LOLBins) and exploiting vulnerabilities in SOHO network devices, Volt Typhoon has demonstrated an ability to maintain persistent access while evading detection. The group’s infiltration of U.S. military networks in Guam is analysed as a case study reflecting Beijing’s broader strategic ambitions in the Indo-Pacific. The findings suggest that China's cyber doctrine is shifting toward pre-positioning for offensive capabilities, enabling covert battlefield preparation in anticipation of geopolitical escalations. The study underscores the necessity for proactive cybersecurity measures, advanced threat intelligence sharing and international collaboration to counter the emerging threats posed by China's evolving cyber warfare strategy